Chapter От молчания-оружия к молчанию-диалогу (и обратно?). Парадоксальный путь Раскольникова в Преступлении и наказании - Dickinson, Sara (Biblioteca di Studi Slavistici, 2023)
From Silence-Weapon to Silence-Dialogue (and Back?). Raskol'nikov's Paradoxical Path in Crime and Punishment. The article explores the phenomenon of silence in Crime and Punishment as an expression of the reverse logic of Dostoevsky's world. Silence in Dostoevsky escapes any attempt at a univocal interpretation, as the use of molchanie and tishina in his novels suggests. It is an emblem of the mistery of human existence because it concerns the character's oscillation between the closure in himself and the opening to the other, between the need to express himself and the awareness of never being able to do it properly. Two levels of the functioning of silence are taken into account: as a stylistic technique used by Dostoevsky to enhance the dramatic effect of some scenes and convey the subtlest nuances of the character's mood; and as a metaphor for Raskol'nikov's dramatic existential journey from self-affirmation to the affirmation of the other's being.